Coral reef communities, habitats and substrates in and near Sanctuary Zones of Ningaloo Marine Park - Cassata, Laura; Collins, Lindsay (CERF, 2008)
As Australia's longest fringing reef, Ningaloo Reef lies close to the mainland of northwest Australia in an area of high tourism potential. The establishment of Sanctuary Zones in and around the northern Ningaloo Marine Park has necessitated improvements in understanding of the biodiversity and distribution of habitats and substrates in the reef lagoon, its seaward barrier and the adjacent shelf environments. Using a combination of video transects in forereef to shelf environments, GPS controlled ground-truthing of colour satellite images and aerial photography for shallow lagoon settings, sixteen habitat types were identified and mapped regionally. Lagoon substrates described in previous reconnaissance were mapped here in greater detail, and some of the first data on poorly known forereef and shelf communities has been analysed from the video transects. There is a strong correlation between reef morphology, inherited substrate type and coral communities across reef lagoons and their associated barriers, where an energy gradient controlled by wave driven and tidal circulation in reef flat and lagoon environments is reflected in the distribution and cover of robust to more delicate coral communities. Morphological controls are less distinct in island-associated habitats, where increased turbidity, differing wave energy and more variable topography result in higher substrate variability and increasing soft coral communities. The data obtained in this study provide a background for management of biodiversity and monitoring of future impacts in some of the Sanctuary Zones likely to experience increased use in the northern Ningaloo Reef.